2006
DOI: 10.1016/j.jaad.2005.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Penile cancer

Abstract: At the completion of this learning activity, participants should be familiar with penile carcinoma, its risk factors, its clinical and histologic presentation, and the treatments currently available for its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
1
17

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 337 publications
(349 reference statements)
2
118
1
17
Order By: Relevance
“…(31) It most commonly presents as invasive squamous cell carcinoma, (31) the incidence of which is over 22 times higher in men who are uncircumcised. (31)(32)(33) In the USA it represents 0.3-0.6% of all male cancers.…”
Section: Penile Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…(31) It most commonly presents as invasive squamous cell carcinoma, (31) the incidence of which is over 22 times higher in men who are uncircumcised. (31)(32)(33) In the USA it represents 0.3-0.6% of all male cancers.…”
Section: Penile Cancermentioning
confidence: 99%
“…(31) It most commonly presents as invasive squamous cell carcinoma, (31) the incidence of which is over 22 times higher in men who are uncircumcised. (31)(32)(33) In the USA it represents 0.3-0.6% of all male cancers. (31) For uncircumcised men in developed countries, lifetime risk of penile cancer is 1 in 600-900, (34) but for circumcised men is only 1 in 50,000-12,000,000.…”
Section: Penile Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This is the most common histological type, accounting for 95% of the cases of penile neoplasms [38,39]. The remaining lesions result from metastasis stemming from tumors in other organs, sarcomas and, very rarely, melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors estimated that HPV-related cancers at penile, anal, and oropharynx sites are rare among men, occurring in about 1-6/100,000 in the general population [39]. It is estimated that penile cancer amounts to 1/100,000 inhabitants in the Western world, while increases in the Latin America area (1.5-3.7/ 100,000) and East Africa (2.8/100,000) [29,55]. HPV DNA is found in approximately 40-50 % of all penile cancers of the penis and epidemiological studies confirmed the predominant role of HPV 16 and 18 [5].…”
Section: Related Pathologiesmentioning
confidence: 99%